1999
DOI: 10.1200/jco.1999.17.8.2396
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Interval Between Preoperative Radiation Therapy and Surgery on Downstaging and on the Rate of Sphincter-Sparing Surgery for Rectal Cancer: The Lyon R90-01 Randomized Trial

Abstract: A long interval between preoperative irradiation and surgery provides increased tumor downstaging with no detrimental effect on toxicity and early clinical results. When sphincter preservation is questionable, a long interval may increase the chance of a successful sphincter-saving surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
445
8
30

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 744 publications
(500 citation statements)
references
References 29 publications
17
445
8
30
Order By: Relevance
“…However, the surgeons were asked before radiotherapy started whether they could perform an anterior resection. The overall recurrence rate was 9%, and in the group of patients having an anterior resection where a sphincter-preserving operation did not seem possible initially, the local recurrence rate was 12% (57). The numbers were small in this trial, but the data must be taken seriously, and it might be dangerous to rely on the downstaging effect caused by preoperative chemoradiotherapy and change surgery from an abdominoperineal procedure to a sphincter-persevering operation.…”
Section: What Type Of Radiotherapymentioning
confidence: 87%
See 1 more Smart Citation
“…However, the surgeons were asked before radiotherapy started whether they could perform an anterior resection. The overall recurrence rate was 9%, and in the group of patients having an anterior resection where a sphincter-preserving operation did not seem possible initially, the local recurrence rate was 12% (57). The numbers were small in this trial, but the data must be taken seriously, and it might be dangerous to rely on the downstaging effect caused by preoperative chemoradiotherapy and change surgery from an abdominoperineal procedure to a sphincter-persevering operation.…”
Section: What Type Of Radiotherapymentioning
confidence: 87%
“…This has been studied in a French trial (57) in which all patients received chemoradiotherapy but were randomly assigned to have surgery immediately after irradiation or after six weeks. More patients had their sphincters preserved if surgery was delayed (76% versus 68%, respectively).…”
Section: What Type Of Radiotherapymentioning
confidence: 99%
“…The main indications being to downstage the disease and organ preservation & relative hypothesis is to tackle the microscopic disease and assessment of response to treatment [1]. Surgery should be performed after a gap of 4-5 weeks for maximum benefit in terms of response and also minimum toxicity as shown by the Lyon R90-01 a randomized trial [7].…”
Section: Neoadjuvant Treatmentmentioning
confidence: 99%
“…Furthermore, in patients presenting with a surgically non-resectable tumor, preoperative RT can cause tumor regression allowing subsequent radical surgery in a substantial proportion of patients (34). It has also been suggested that preoperative RT facilitates sphincter-preserving procedures by decreasing the size of the tumor (33,35), however, this was not significant in a Cochrane systematic review (36). Thus, preoperative RT is now considered standard treatment in LARC at least in the European health community (37)(38)(39).…”
Section: Neoadjuvant Radiotherapy (Rt)mentioning
confidence: 99%